Complexity of approximation problems - Korneichuk, N. P. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We consider some aspects of optimal encoding and renewal related to the problem of complexity of the ε-definition of functions posed by Kolmogorov in 1962. We present some estimates for the ε-complexity of the problem of renewal of functions in the uniform metric and Hausdorff metric.